Is It Possible to Ignore Problems Rising During Vertical Drilling? A Review - Saleem Qadir Tunio, Saleem (Maxwell Scientific Organization, 2011, 2011)
The drilling process in petroleum industry is directly proportional with economics and if even a small problems encounters on any point during drilling will might results a commercial loss (i.e. economics and time factor). This study is based on the study of all those hindrances/problems often encounters during vertical drilling and ways to combat against those problems. Now, these days although the drilling have been an advanced practice but the problems are still of same nature like (bore-hole instability, loss-circulation, drill pipe sticking, gas cuts in a shallow formation, salt dome, kick and back flow). This study focuses above problems which are not natural but it is due to human error or may be the improper handling of the tool during the operation but these are critical with reference to the time factor and also budgeting is there. So, if these occur then the possible remedial actions in order to save the time factor as well as the economics are kept and handled accordingly. This may involve, the proper design of drilling components regarding given geophysical data of formation, proper usage of drilling fluid to avoid bit balling, formation sloughing, maintaining hydrostatic pressure and proper usage of blow out preventor to control abnormal pressures, so that a good drilling performance will be taken into account by setting up a benchmarking process that is termed to be as “a necessity for survival”.